J/ψ in high-multiplicity pp collisions: lessons from pA collisions - Kopeliovich, Boris Z.; Pirner, Hans J.; Potashnikova, I. K.; Reygers, Klaus; Schmidt, Iván (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
Gluons at small x in high-energy nuclei overlap in the longitudinal direction, so the nucleus acts as a single source of gluons, like higher Fock components in a single nucleon, which contribute to inelastic collisions with a high multiplicity of produced hadrons. This similarity helps to make a link between nuclear effects in pA and high-multiplicity pp collisions. Such a relation is well confirmed by data for the J/Ψ production rate in high-multiplicity pp events measured recently in the ALICE experiment. Broadening of J/Ψ transverse momentum is predicted for high-multiplicity pp collisions.
Gesehen am 25.03.2021